A Review Study of Numerical Analysis: Exploring the Intersection of Mathematics, Algorithms, and Computation (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Numerical Research and Implementations occurs for the discussion and propagation of algorithms and numerical techniques in mathematics, mathematical mechanics, and other applied fields. The focus should be on mathematical structures and modern analytical techniques, or the implementation of current methods. The aim is to devise algorithms that provide quick and accurate answers to mathematical problems for scientists and engineers, nowadays using computers. The word continuous is important numerical and analytical concerns actual (or complex) variables, as opposed to discrete variables, which are the realm of software engineering.